A Study of Overtime Practice in Software Development Projects in Indonesia - Permana, Arena Bayu Chandra (2017)
Overtime is known as a common practice in software development projects, even though some studies have shown that it also brings negative impacts. Previous studies related to this topic have been conducted in many regions across the world, but there is no existing research in such topic in Indonesia. Therefore, this dissertation focuses to observe the overtime practice in software development projects in Indonesian-based organizations. The research methodology used in this study is qualitative case studies. Data is obtained from the interview process in two different organizations in Indonesia, with each represents different category: government organizations and private companies. The main conclusions resulted from this study is that overtime is typically a common practice performed in software development projects in Indonesia, with requirement changes as the main factor. This study also shows that overtime has more drawbacks than benefit to both workers and the project. Lastly, the methodology used in the project is shown to have strong relationship with the amount of overtime needed. Therefore, changing the project methodology may become an alternative solution to deal with overtime issue.